Curriculum Development for the Subject of “Jadi Pendamping Adik” in Grade X of Senior High School - Sera, Marianus A.G; Situmorang, Robinson; Siregar, Eveline (LPPM Undiksha, 2021)
The curriculum is one component of education that has an important role in determining the quality of education. Therefore, curriculum development is very important. This study aims to develop a curriculum for the subject of